Geochemical characteristics and water quality assessment of trace elements in geothermal springs in the Gulu-Yadong rift, Tibetan Plateau. (June 2023) - Sun, Yutao; Zhou, Xiaocheng; He, Miao; Yan, Yucong; Tian, Jiao; Li, Jingchao; Dong, Jinyuan; Zhang, Yue
Highlights: As, Cr, B and F were the trace elements with high concentrations in the Gulu-Yadong rift. Water quality throughout the whole rift are heterogeneous. Subduction-related magmatic processes, leaching and water-rock interaction are the controlling factors of trace elements in the thermal water. Trace elements in geothermal water is a non-negligible environmental and health issue in the Tibetan Plateau. Abstract: Thermal springs are enriched in many trace elements that are closely related to environmental and human health. The occurrence of trace elements in groundwater systems is one of the most significant environmental and public health concerns. The northward subduction of the Indian continental lithosphere beneath the Asian continent has produced an ongoing continental subduction zone. The Tibetan Plateau serves as the 'Water Tower of Asia', supplying drinking water to more than one billion residents in Asia. In this study, eighteen geothermal springs in the Gulu-Yadong Rrift (GYR) were selected for investigation of the geochemical characteristics of their trace elements. The geological process–related geochemical characteristics of trace elements in geothermal springs in the GYR were quantitatively assessed. The results indicated that there were high concentrations of Cr, As, B, and F in the geothermal waters in the GYR. The concentrations of Cr, As and B greatly exceeded the World Health Organization (WHO) guidelines for drinking water. The water quality throughout the whole rift was spatially heterogeneous. The concentrations of trace elements in only six geothermal springs were within the guidelines of the WHO, while the concentrations of trace elements in eleven geothermal springs considerably exceeded the WHO guidelines. Continental subduction–related magmatic processes, leaching and water-rock interactions may be the main factors controlling trace elements in the geothermal water. The deep circulation of the thermal water facilitated the addition of upwelling hot materials and magmatic fluids into the shallow aquifers, as well as enhancing the water-rock interactions. The results of this study indicate that geological processes have a large influence on the geochemical characteristics of trace elements in geothermal springs in the Tibetan Plateau. It is a non-negligible environmental and health issue in the plateau.